Correlation Between Chronic Periodontal Disease, Systemic Inflammatory Blood Markers and Severity of Chronic Obstructive Pulmonary Disease (COPD): A Cross-Sectional Study - Muhammad Tariq Hamayun Khan, Saher Sultan, Usman Mahmood, Sheeba Faryal, Muhammad Omar Niaz, Mobin Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic Obstructive Pulmonary Disease (COPD) and Chronic Periodontal Disease (CPD) are both widespread chronic inflammatory disorders that significantly impact global health. Emerging evidence suggests a potential link between these two conditions, mediated through systemic inflammation. This study aimed to assess the correlation between the severity of CPD and COPD and to evaluate the role of systemic inflammatory blood markers as possible biological mediators. Methods: A cross-sectional analytical study was conducted on 75 COPD patients aged 40–70 years at tertiary care centers in Peshawar and Lahore from June 2022 to March 2023. COPD severity was determined using spirometry per GOLD 2023 guidelines. Periodontal status was assessed using Plaque Index (PI), Gingival Index (GI), Probing Pocket Depth (PPD), and Clinical Attachment Loss (CAL). Systemic inflammatory markers—C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), total leukocyte count (TLC), and neutrophil-to-lymphocyte ratio (NLR)—were measured and analyzed for associations with disease severity using SPSS version 26. Results: Patients with moderate to very severe COPD exhibited higher levels of inflammatory markers, especially ESR and TLC. Similarly, ESR was elevated in patients with severe periodontitis, indicating chronic systemic inflammation. Although CRP and TLC were higher in mild periodontal cases, they slightly declined with increasing severity. The co-existence of moderate to severe CPD in most patients with advanced COPD stages highlighted a potential correlation between the two conditions. Conclusion: The study supports a significant association between CPD and COPD severity, potentially mediated by systemic inflammation. Integrating dental care into COPD management may reduce systemic inflammatory burden and improve patient outcomes. Keywords: Chronic Obstructive Pulmonary Disease (COPD), Chronic Periodontal Disease (CPD), Systemic Inflammation, C-reactive Protein (CRP), Erythrocyte Sedimentation Rate (ESR), Neutrophil-to-Lymphocyte Ratio (NLR), Oral-Lung Axis.